Abiogenic Fischer–Tropsch synthesis of methane at the Baogutu reduced porphyry copper deposit, western Junggar, NW-China - Cao, M.; Qin, K.; Li, G.M.; Evans, Noreen; Jin, L.Y. (Pergamon, 2014)
Methane is widely developed in hydrothermal fluids from reduced porphyry copper deposits, but its origin remains enigmatic. The occurrence of methane in fluid inclusions at the Late Carboniferous Baogutu reduced porphyry copper deposit in western Junggar, Xinjiang, NW-China, presents an excellent opportunity to address this problem. A systematic study including fluid inclusion Laser-Raman and CO2–CH4 carbon isotope analyses, igneous and hydrothermal mineral H–O isotope analyses, and in situ major, trace element and Sr isotopic analyses of hydrothermal epidote was conducted to constrain the origin of CH4 and CH4-rich fluids. The δ2H and δ18O of water in equilibrium with igneous biotite ranges from −65.0‰ to −66.0‰ and +7.2‰ to +7.4‰, respectively, indicating notable degassing of probably supercritical fluids in the magma chamber. The wide range of δ2H (−58.0‰ to −107.0‰, n = 23) for water within quartz suggests the existence of significant hydrothermal fluid boiling. Water–rock interaction is the most likely mechanism leading to the wide range of δ18O values for water in vein quartz with water/rock ratios (wt.% in O) of 0.15 to 0.75 and 0.13 to 0.46 for a closed and open system, respectively.Detailed Laser-Raman analyses indicate CO2 in apatite included in granodiorite porphyry phenocrystic biotite that records the carbon species of the early stage magmatic stage, whereas later hydrothermal fluids containing CH4 with trace or without CO2 are found in inclusions of vein quartz. We propose that CH4 is probably transformed from CO2 by Fischer–Tropsch type reactions at 500 °C, assumed from CO2–CH4 C isotope equilibrium. The (87Sr/86Sr)i of hydrothermal epidote yields values of 0.70369–0.70404, consistent with that reported for the whole rocks. The δ13CCH4CCH4 (−28.6‰ to −22.6‰) and δ2HCH4HCH4 (−108.0‰ to −59.5‰) are characteristic of abiogenic methane. The measured δ13CCO2δ13CCO2 shows a slightly depleted 13C (−13.5‰ to −7.2‰) relative to upper mantle (−6‰), probably due to the combined effects of minor (less than 0.5%) sedimentary organic matter contamination in the mantle and carbon isotope fractionation occurring during late degassing. Combining the results indicates that CO2 likely originated from the upper mantle with trace addition of sedimentary organic matter. During the uplift or emplacement of the granitoids, significant degassing caused the depletion of 13C and 2H. As the granitoids cooled, notable hydrothermal fluid boiling and water–rock interaction produced the depletion of 2H and 18O, respectively, and the magmatic CO2 was reduced to CH4 by Fischer–Tropsch type reactions that probably occurred during Ca–Na and potassic hydrothermal alteration.